Development of the Technique of Assessment of Banking Risks of Long-Term Crediting of Investments (On the Example of Banks of Sevastopol) - Dremova, Ulyana Viktorovna (Economy of Regions, 2015)
The external destabilizing factor - financial crisis - has significantly influenced on the level increase of riskiness of the banking credit operations. Taking into account that the increased level of risk follows long-term credits, these operations has been influenced the most, that can be as one of the constraining conditions for the provision of bank long-term credit resources. It, in turn, causes the need to develop the risk assessment technique of long-term credits in regulation of banks’ long-term credit operations. As the risk assessment of credit operations in banking practice is generally limited to the calculation of credit risk, it is efficient to consider the scientifically reasonable approach to a risks assessment of long-term crediting including influence of private risks for the purpose of carrying out the generalized assessment of riskiness both separate types of long-term credits, and a long-term credit port/olio in general. The offered method is based on the calculation of aggregate risk coefficient of the long-term credits, calculated by means of mathematical method of principal component. In the work, it is offered to per/orm an assessment of private risks by means of statistics: the expectation value, mean square deviation, and the coefficient of a variation. The use of the principal components’ method at the risk assessment of long-term crediting meets such requirements as a lack of value judgment, accounting of specific features of private risks of long-term credits, mathematical validity. It gives the chance to apply the offered risk assessment method of long-term credits in banking. The conclusion is made that the application of an aggregative risk indicator of a long-term crediting will allow banks to trace more accurately the level of riskiness of a long-term credit port/olio and separate types of long-term credits that will strengthen the bank in/ormation and analytical base on risk regulation in the field and will expand tools of bank management.